Organic crystalline monolayers for ideal behaviours in organic field-effect transistors. Issue 36 (1st September 2021) - Xiao, Mingchao; Zhang, Xi; Liu, Jie; Gao, Xike; Liu, Chuan; Liu, Zitong; Wang, Shuai; Jiang, Lang
Abstract : In this work, ideal OFETs have been obtained by a facile and effective method, i.e. phase-separation between polymer and small molecules, and the generated monolayer crystals are beneficial for reducing contact resistance and interfacial trap density. Abstract : Organic field-effect transistors (OFETs) with accurate electrical characterization and parameterization of physical properties are essential for fundamental studies and commercial applications. However, with the improvement of mobility, non-ideal behaviours have been widely observed. The non-ideal behaviours not only have an adverse impact on extracting the electrical parameters but also hinder their commercial applications. In this work, we report a simple yet effective method by using phase separation to realize ideal transistor behaviours. The crystalline monolayers could be easily obtained on the top and bottom surfaces of polymers by using phase separation. We demonstrate that the use of crystalline monolayers can effectively reduce contact resistance and interface trap density, which could eliminate the gate-voltage dependent transfer behaviours without significantly sacrificing mobility. This work provides effective solutions for realizing ideal (− I DS ) 1/2 – V G behaviours in OFETs, which are supposed to propel their fundamental studies and practical applications.